In vivo feasibility test using transparent carbon nanotube‐coated polydimethylsiloxane sheet at brain tissue and sciatic nerve. Issue 6 (3rd April 2017) - Wang, Caifeng; Oh, Sangjin; Lee, Hyun Ah; Kang, Jieun; Jeong, Ki‐Jae; Kang, Seon Woo; Hwang, Dae Youn; Lee, Jaebeom
Abstract: Carbon nanotubes, with their unique and outstanding properties, such as strong mechanical strength and high electrical conductivity, have become very popular for the repair of tissues, particularly for those requiring electrical stimuli. Polydimethylsiloxane (PDMS)‐based elastomers have been used in a wide range of biomedical applications because of their optical transparency, physiological inertness, blood compatibility, non‐toxicity, and gas permeability. In present study, most of artificial nerve guidance conduits (ANGCs) are not transparent. It is hard to confirm the position of two stumps of damaged nerve during nerve surgery and the conduits must be cut open again to observe regenerative nerves after surgery. Thus, a novel preparation method was utilized to produce a transparent sheet using PDMS and multiwalled carbon nanotubes (MWNTs) via printing transfer method. Characterization of the PDMS/MWNT (PM) sheets revealed their unique physicochemical properties, such as superior mechanical strength, a certain degree of electrical conductivity, and high transparency. Characterization of the in vitro and in vivo usability was evaluated. PM sheets showed high biocompatibility and adhesive ability. In vivo feasibility tests of rat brain tissue and sciatic nerve revealed the high transparency of PM sheets, suggesting that it can be used in the further development of ANGCs. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 105A: 1736–1745, 2017.